Towards Finer Granularity in Metadata - Gerhard Budin; Heinrich Kabas; Karlheinz Mörth (Journal of the Text Encoding Initiative)
In early 2010, the Austrian Academy of Sciences’ ICLTT instituted an experiment in selective metadata creation for a medium-sized collection (